MENELISIK PENGAKUAN DAN PERLINDUNGAN HAK-HAK ASASI POLITIK PASCA PERUBAHAN UUD 1945 - Jatmiko, Bayu Jatmiko (Jurnal Panorama Hukum, 2018)
The concept of the relationship between state law and human rights (HAM) is an important thing in the concept of a modern state. Although the theory of thinking about human rights is divided universally or in particular, Indonesia is trying to escape from this debate. So that historically the regulation of human rights by the Indonesian state actually preceded the arrangement of human rights by the United Nations (UN), then included it in the articles governing Political Rights